2010
DOI: 10.1088/0004-637x/710/1/248
|View full text |Cite
|
Sign up to set email alerts
|

POWERFUL H2LINE COOLING IN STEPHAN's QUINTET. I. MAPPING THE SIGNIFICANT COOLING PATHWAYS IN GROUP-WIDE SHOCKS

Abstract: We present results from the mid-infrared spectral mapping of Stephan's Quintet using the Spitzer Space Telescope 10 . A 1000 km s −1 collision (t col = 5 × 10 6 yr) has produced a group-wide shock and for the first time the large-scale distribution of warm molecular hydrogen emission is revealed, as well as its close association with known shock structures. In the main shock region alone we find 5.0 ×10 8 M ⊙ of warm H 2 spread over ∼ 480 kpc 2 and additionally report the discovery of a second major shock-exci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
214
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(232 citation statements)
references
References 67 publications
16
214
2
Order By: Relevance
“…The pixel sizes are 1.8 , 2.45 , and 5 at 16, 24, and 70 μm, respectively. Except for the 70 μm image, we direct the reader to Cluver et al (2010) for a description of the observational details and data reduction. The upper right panel of Fig.…”
Section: Spitzer Ir Imaging and Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The pixel sizes are 1.8 , 2.45 , and 5 at 16, 24, and 70 μm, respectively. Except for the 70 μm image, we direct the reader to Cluver et al (2010) for a description of the observational details and data reduction. The upper right panel of Fig.…”
Section: Spitzer Ir Imaging and Spectroscopymentioning
confidence: 99%
“…Observations with the infrared spectrograph (IRS, Houck et al 2004) onboard the Spitzer Space Telescope have revealed a powerful mid-infrared (mid-IR) H 2 rotational line emission from warm (∼10 2 −10 3 K) molecular gas in the SQ shock (Appleton et al 2006;Cluver et al 2010). The H 2 emission is extended not only over the whole ridge, but in several other structures, including an extension towards the Seyfert galaxy NGC 7319, and the intergalactic starburst SQ-A (Xu et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The best studied example is Stephan's Quintet (SQ = HCG92), where HI and molecular studies show that almost all of the cold interstellar medium (ISM) now resides in the intragroup medium (Williams et al 2002;Gao & Xu 2000;Guillard et al 2012). Strong dissipative processes, in addition to gravity, are clearly at work on a large scale in this system, leading to extensive shock heating in the interfaces between galaxies and the intragroup medium, as is evident by the presence of hot X-ray gas, warm molecular hydrogen, and diffuse ionized carbon (Trinchieri et al 2005;O'Sullivan et al 2009;Appleton et al 2006;Cluver et al 2010;Appleton et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Powerful high-velocity dispersion molecular hydrogen is associated with the intergalactic shock wave (Appleton et al 2006;Guillard et al 2009). About 5 × 10 8 M of warm H 2 spread over ∼480 kpc 2 were found in the main shock region (Cluver et al 2010). In addition, CO(1−0), (2−1) and (3−2) line emission have been detected in this region with complex profiles, spanning a velocity range ∼1000 km s −1 (Guillard et al 2012).…”
Section: Introductionmentioning
confidence: 99%